Assimilative Capacity of Air Pollutants Using Emission Inventory and Dispersion Model - Huboyo, Haryono Setiyo; Samadikun, Budi Prasetyo; Manullang, Okto Risdianto; Khasanah, Nurul (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2025)
Air pollution in urban areas will increase along with increasing population activity. This study, with the location of Magelang Regency, examines the carrying capacity and capacity of air pollution. The study began with the identification of emission inventories for transportation, household, waste burning and industrial activities. The results of the inventory were used to examine the distribution of air pollutants. The results of the emission inventory in Magelang Regency showed that the transportation sector was the dominant contributor of emissions compared to the waste, household and industrial sectors with an emission load of 2-3.5 times higher. The transportation sector contributes dominantly to the NO2 parameter (94%) and PM parameter (72%), with a relatively similar contribution to the industrial sector in the SO2 parameter (40%). Dispersion modeling showed that the distribution of emissions was even throughout Magelang Regency and showed an accumulation of emissions, especially for the NO2 parameter which was centered on the arterial and collector road networks. When compared to the Ambient Air Quality Standard in Indonesia, the maximum concentration values for SO2, NO2 and PM parameters are still below the quality standard. However, the NO2 parameter needs to be considered because its concentration value has reached 75% of AAQS. Based on environmental carrying capacity, Tegalrejo, Mungkid and Mertoyudan sub-districts are still in good condition, while Secang and Tempuran sub-districts need to carry out mitigation and emission reduction efforts so that air quality is maintained because the air quality index shows moderate and unhealthy quality respectively